Regression of high-grade squamous intraepithelial cervical lesions and associated risk factors (RECER) - Dostalek, Lukas; Brynda, Daniel; Marek, Radim; Hederlingova, Julia; Tripac, Irina; Nemejcova, Kristyna; Slovackova, Miroslava; Zima, Tomas; Cibula, David; Slama, Jiri (International journal of gynecological cancer, 2025)
BACKGROUND: Avoiding conization may reduce the risk of pre-term labor in future pregnancies, making conservative treatment of high-grade cervical dysplasia an increasingly discussed approach, especially for younger patients. However, data on the integration of individual predictive factors into routine clinical practice remain limited. PRIMARY OBJECTIVE: The primary objective of the Regression of High-Grade Squamous Intraepithelial Cervical Lesions and Associated Risk Factors (RECER) study is to assess the rate of spontaneous regression in high-grade cervical squamous dysplasia (cervical intraepithelial neoplasia [CIN] 2 and 3) and identify associated predictive factors within clinical practice, without necessitating conization. STUDY HYPOTHESIS: We hypothesize that the characterization of cervical lesions, including colposcopic findings and patient-specific factors, along with a sufficient rate of spontaneous regression, will aid in identifying a subgroup of patients who may derive the greatest benefit from conservative management of high-grade cervical lesions. TRIAL DESIGN: The RECER trial is a multi-center prospective cohort study. Patients with histologically confirmed high-grade squamous intraepithelial lesions (CIN 2 or 3) undergo colposcopic assessments every 4 months. Colposcopic images are compared to evaluate lesion dynamics. In case of progression, conization is indicated, whereas in case of regression, documentation of a biopsy with low-grade dysplasia (CIN 1) or no dysplasia is required. Patients with stable disease are further followed up. MAJOR INCLUSION/EXCLUSION CRITERIA: Patients aged 18 to 40 years with bioptically confirmed high-grade lesion (CIN 2 or 3), a fully visible squamo-columnar junction, and a willingness to undergo conservative management can be included. Excluded are patients with unsatisfactory colposcopy, pregnancy, glandular lesions, invasive disease, or a history of treatment for severe cervical dysplasia. PRIMARY ENDPOINT: The primary end point is the regression rate of high-grade cervical dysplasia. SAMPLE SIZE: 300 patients ESTIMATED DATES FOR COMPLETING ACCRUAL AND PRESENTING RESULTS: As of October 2024, a total of 127 patients have been recruited from 4 participating sites across 3 countries. Estimated date of last patient enrollment: September 2026; estimated date for results presentation: January 2028. TRIAL REGISTRATION: Clinicaltrials.gov: NCT06147388.
Keywords: Cervical Cancer; dospělí; Female; Adult; mladý dospělý; ženské pohlaví; High-Grade Cervical Dysplasia; Multicenter Studies as Topic; lidé; Neoplasm Grading; Squamous Intraepithelial Lesions of the Cervix; dlaždicová intraepiteliální léze cervixu; nádory děložního čípku; Methylation; konizace děložního čípku; Risk Factors; stupeň nádoru; multicentrické studie jako téma; prospektivní studie; Observational Studies as Topic; pozorovací studie jako téma; Prospective Studies; Conization; Young Adult; spontánní remise; Remission, Spontaneous; rizikové faktory; Colposcopy; Uterine Cervical Neoplasms; kolposkopie; Uterine Cervical Dysplasia; Conservative Management; dysplazie děložního hrdla; Humans